Leisure-time physical activity alone may not be a sufficient public health approach to prevent obesity - A focus on China - Bauman, A.; Allman-Farinelli, M.; Huxley, Rachel; James, W. (Wiley-Blackwell Publishing Ltd., 2008)
Much small-scale research has identified the role of physical activity in obesity prevention. This is the 'energy expenditure' side of the energy balance equation. Although around half an hour of daily moderate-intensity physical activity is required for cardiovascular health and disease prevention, the quantum of physical activity required for obesity prevention and weight loss is around 60-90 minutes per day. This amount of physical activity is difficult to achieve through leisure time physical activity (LTPA) alone, and additional energy expenditure is needed in the domains of active transport, occupation activity and in domestic settings. Modeling of 24-hour energy expenditures demonstrate the need for 'active living', namely energy expenditure over and above that due to LTPA, for weight loss and obesity prevention. The consequences of this for developing countries such as China are the need to focus on preventing the declines in energy expenditure attributable to urbanization, industrialization, and motor vehicle dependence. These will pose policy challenges in the developing world, if they are to be taken seriously as obesity prevention strategies. © 2007 The Authors.